Inculcating the practice of reflection among medical students: Role of teachers - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Muller Journal of Medical Sciences and Research, 2021)
Over the years, different regulatory and professional organizations have emphasized the need for medical students to reflect upon their daily learning or clinical interactions to ensure deep learning. An extensive search of all materials related to the topic was carried out in the PubMed search engine, and a total of seven articles were selected for the review. However, we must admit that the practice of reflection is not easy to inculcate, and amid the packed curriculum, it becomes the responsibility of the medical teachers to create opportunities for the students to reflect upon on a regular basis. The best approach for encouraging reflection by medical students will be to not make reflection as an add-on activity, but as a strategy which will enhance meaningful learning and improvement in daily clinical interactions. In conclusion, reflection is an important approach to ensure deep learning among medical students. However, it is the responsibility of all teachers to first teach them about reflection and then use the tool of reflection for the betterment of the students in the entire training period.